2014
DOI: 10.1016/b978-0-12-800256-8.00002-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Structure on Reactivity in Alkene Metathesis

Abstract: Alkene metathesis has grown from a niche technique to a common component of the synthetic organic chemistry toolbox, driven in part by the development of more active catalyst systems, or those optimized for particular purposes. While the range of synthetic chemistry achieved has been exciting, the effects of structure on reactivity have not always been particularly clear, and rarely quantified. Understanding these relationships is important when designing new catalysts, reactions, and syntheses. Here, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 203 publications
(309 reference statements)
0
4
2
Order By: Relevance
“…26c It has been observed in several cases that the gemdisubstitution of a diene backbone favors cyclization reactions. 29 However, the observed reversal of the E/Z stereoselectivity in the current study seems counterintuitive. The E/Z geometry of a metathesis product is controlled at the metallacyclobutane intermediate, where the alkyl or aryl substituents R are remote from the four-membered ring (Scheme 4).…”
Section: Synthesiscontrasting
confidence: 80%
“…26c It has been observed in several cases that the gemdisubstitution of a diene backbone favors cyclization reactions. 29 However, the observed reversal of the E/Z stereoselectivity in the current study seems counterintuitive. The E/Z geometry of a metathesis product is controlled at the metallacyclobutane intermediate, where the alkyl or aryl substituents R are remote from the four-membered ring (Scheme 4).…”
Section: Synthesiscontrasting
confidence: 80%
“…In contrast, an associative interchange mechanism could also rationalize the observed KIE for dx -DME , where steric clash between the NHC and the incoming monomer would be alleviated by the shorter C–D bonds. Ru benzylidene precatalysts like 3 have been proposed to initiate via an associative interchange mechanism . In particular, Plenio and co-workers showed that initiation of 3 and related derivatives is a combination of both an associative interchange and dissociative exchange mechanism, with smaller substrates favoring the associative interchange pathway .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ru benzylidene precatalysts like 3 have been proposed to initiate via an associative interchange mechanism. 32 In particular, Plenio and co-workers showed that initiation of 3 and related derivatives is a combination of both an associative interchange and dissociative exchange mechanism, with smaller substrates favoring the associative interchange pathway. 33 Lloyd-Jones and co-workers have also shown that the reaction of third generation Ru catalysts with vinyl ethers proceeds via a combination of both mechanisms, with an associative interchange mechanism dominating at higher substrate concentration, 34 supporting calculations by Grela.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Importantly, however, calculations performed on nontruncated GII and GIIm show the same trends in magnetic shielding as a function of the systematic increase in the internuclear Ru–P distances (see SI, Table S1 and Figure S8). It should be noted that dispersion corrections, while critical for treating the energy of ligand loss and binding in these complexes, , are less relevant to assessment of CS tensor values …”
Section: Resultsmentioning
confidence: 99%